Identification of TLR2 as a Key Target in Neuroinflammation in Vascular Dementia - Wang, Yuye; Lv, Shuang; Zhou, Xiao; Niu, Xiaoqian; Chen, Leian; Yang, Ziyuan; Peng, Dantao (Frontiers in Genetics, 2022)
Vascular Dementia (VaD) is the second most common cause of dementia. At present, the precise molecular processes of VaD are unclear. We attempted to discover the VaD relevant candidate genes, enrichment biological processes and pathways, key targets and the underlying mechanism by microarray bioinformatics analysis. We selected GSE122063 related to the autopsy samples of VaD for analysis. We firstly took use of Weighted Gene Co-expression Network Analysis (WGCNA) to achieve modules related to VaD and hub genes. Secondly, we filtered out significant differentially expressed genes (DEGs). Thirdly, Significant DEGs then went through Geno Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Fourthly, Gene Set Enrichment Analysis (GSEA) analyses were performed. At last, we constructed protein-protein interaction (PPI) network. The results showed that the yellow module was most correlated with VaD and we finally identified 21 hub genes. Toll-like receptor 2 (TLR2) was the top hub gene and was strongly correlated with other possible candidate genes. 456 significant DEGs were filtered out and genes were found to be enriched in the Toll receptor signaling pathway and several other immune-related pathways. Besides, GSEA results showed that similar pathways were significantly over-represented in TLR2-high samples. In the PPI network, TLR2 was still an important node with high weight and combined scores. We concluded that the TLR2 act as a key target in neuroinflammation which may participate in the pathophysiological process of VaD.